College Students' Preferences for Test Accommodations. (June 2014) - Lewandowski, Lawrence; Lambert, Tonya L.; Lovett, Benjamin J.; Panahon, Carlos J.; Sytsma, Marcia R.
College students with ( n = 137) and without disabilities ( n = 475) were surveyed about their perceptions of using various types of test accommodations. Results indicated that extended time was perceived as having a positive effect by the most students (>87% of both groups), followed by separate room testing and extra breaks (>60% of both groups). Students with disabilities rated separate room, a scribe, reader, and word processor more positively than did nondisabled students. Students generally felt that test accommodations on high-stakes exams would be more beneficial than on classroom tests. A significant number of students felt that everyone should have access to test accommodations, and/or that tests should be redesigned to remove the need for accommodations. Implications of these findings for practice and future research are discussed.